Speed Reading Method to Improve Reading Comprehension Skills among Fifth-Grade Students Primary School - Picarima, Thomas; Ririhena, Ribka L.; Maipauw, Musa Marsel (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
This research is motivated by the low reading comprehension skills of fifth-grade students at State Elementary School 41 Ambon. This problem has a significant impact on the overall learning process and students' academic achievement. The main objective of this research is to strengthen the reading comprehension skills of fifth-grade students in elementary school through the application of the speed-reading method. This research employs Classroom Action Research (CAR) in two cycles, utilizing the Kemmis and McTaggart model. Each CAR cycle consists of planning, implementation, observation, and reflection stages. The research subjects were 20 fifth-grade students at State Elementary School 41 Ambon. The results of the study showed a significant increase in students' reading comprehension after the application of the speed-reading method. The study observed an increase in student activity during the learning process, which rose from 72% in Cycle I to 93.18% in Cycle II. The study also observed an increase in students' learning completeness, specifically in reading comprehension, from only 30% in Cycle I to 100% in Cycle II. The conclusion of this research is that the speed-reading method is effective in improving elementary school students' reading comprehension skills in Indonesian language learning. This research aims to furnish practical solutions and innovative pedagogical models for educators to address reading comprehension challenges in the classroom, while also serving as a foundation for the advancement of speed-reading techniques at the elementary education level.